2011
DOI: 10.1080/14664208.2011.541390
|View full text |Cite
|
Sign up to set email alerts
|

Gender representation in a Hong Kong primary English textbook series: the relationship between language planning and social policy

Abstract: Language-in-education planning in the form of materials planning has an important role to play in achieving a society's social goals. Gender stereotyping has been found in previous language textbook studies. Although gender bias has declined, some recent studies suggest that it still exists. This study analysed the content and language of a recently published Hong Kong English language textbook series for grade one students to explore its gender representation. The results of the study showed that males and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 12 publications
2
18
3
2
Order By: Relevance
“…In addition, there is only one male teacher as opposed to three female teachers. This is inline with Yang's (2011) research finding in Hongkong textbooks, in which among 24 characters of teachers, none of them is male. Yi's (2002) study in Blumberg (2009) also revealed similar condition English textbooks in China, where all teachers illustrated in the text are females.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, there is only one male teacher as opposed to three female teachers. This is inline with Yang's (2011) research finding in Hongkong textbooks, in which among 24 characters of teachers, none of them is male. Yi's (2002) study in Blumberg (2009) also revealed similar condition English textbooks in China, where all teachers illustrated in the text are females.…”
Section: Discussionsupporting
confidence: 86%
“…To find out if gender bias exists in the EFL textbooks for Senior High School students in Indonesia, a model of analysis done by Yang (2011) was used. In her model of analysis, a tally was done to count the appearance of each gender in the textbooks.…”
Section: Methodsmentioning
confidence: 99%
“…Since primary school, Carl received schooling in a boys' school. Possessing a traditional perspective towards the relationship between gender and language ability, he believed that females were more capable of mastering a language (Yang, 2011). He attached gender difference to the lower English ability among his classmates.…”
Section: Out-of-class Peer-based Learning In English: Constraintsmentioning
confidence: 99%
“…Textbook materials planned are closely related to wider educational and social context (Yang, 2011). Indonesian social context, with different cultures, consists of different views about gender, and from the cultures students can learn how female and male play their social role.…”
Section: Introductionmentioning
confidence: 99%